Banquets et rites collectifs au ve s. av. J.-C. au sein de l’habitat de la Monédière à Bessan (Hérault) : caractérisation et signification d’une fosse hors norme et des dépôts associés - Alexandre Beylier; Éric Gailledrat; Anne-Marie Curé; Cécile Dubosse; Luke Howarth; Ariadna Nieto Espinet (Gallia)
Rescue excavations conducted in 2014 at the protohistoric dwelling site of “La Monédiere” in Bessan (Hérault, South of France) have revealed several unexpected discoveries. This excavation brought to light an unparalleled excavated structure in Gaul or the north-western Mediterranean region. This exceptionally large pit was used for the deposition of an important assemblage of artefacts between 475 and 420 BC, corresponding to the final phases of the settlement. These artefacts consist of ceramic vessels associated with the consumption of wine, accompanied by atypical faunal remains, indicating beef consumption, as well as several objects rarely observed in a native context. The assemblage recovered from this pit appears to be related to the banquet sphere and raises new questions relating to Symposion practices in Mediterranean Gaul. This assemblage cannot be merely considered as representative of domestic waste. It is clearly linked to the practice of commensality—possibly public events—with ritual connotations, at which some of the participants could have been Greek. The organization of these final deposits and the context appear to be indicative of a closing ceremony. It is tempting to consider these events in parallel with the profound changes affecting the region at that time, notably with the emergence of the nearby Greek colony of Agde.